Analysis Of Service Quality Factors With Outpatient Satisfaction at Titi Papan Puskesmas Year 2017 - T.Arif Munandar Harahap; Ivan Elisabeth Purba (Akupun Tour Publisher, 2023)
Background: Health services are an important factor in improving the health and welfare of every human being throughout the world. Good health services are a community need and often become a benchmark in the success of development. Patient satisfaction in assessing good service quality is an important measurement that is fundamental to service quality. Purpose: The purpose of this study was to determine the factors related to patient satisfaction with services at the Titi Papan Health Center, Medan Labuhan District. Method : The design of this study uses descriptive analysis with a cross sectional approach. The population is all new patients who come for treatment at the Titi Papan Health Center in August-September 2017. The sample in this study is 115 respondents who come for treatment at the Titi Papan Health Center which is determined by the case accidental sampling technique. Results: The results of the study were analyzed with SPSS using the chi square test. The results showed that the majority of patients' perceptions of services at the Puskesmas were good and the majority of patients' satisfaction with services at the Puskesmas were satisfied. The results of the hypothesis test showed that there was a relationship between direct evidence (p=0.000), reliability (p=0.000), responsiveness (p=0.000), assurance (p=0.000), and empathy (p=0.000) with patient satisfaction. Disscusion and Conclusion : The conclusion of this study is that there is a significant relationship between tangibles, reliability, responsiveness, assurance, and empathy with outpatient satisfaction at the Titi Papan Health Center. Suggestions to the Puskesmas for the future can compile and adopt policies to make it easier for services in an effort to improve the quality of Titi Papan Health Center health services.